Complete characterization of ocean color radiometers - Vabson, Viktor; Ansko, Ilmar; Duong, Kim; Vendt, Riho; Kuusk, Joel; Ruddick, Kevin; Bialek, Agnieszka; Tilstone, Gavin H.; Gossn, Juan Ignacio; Kwiatkowska, Ewa (Frontiers in Remote Sensing, 2024)
As for most or all Earth Observation measurands, verifying and validating water-leaving radiance measurements from space for an accurate derivation of Ocean/Water Colour biogeophysical products is based on concurrent high-quality fiducial reference measurements (FRM) carried out on the ground or water body. The Ocean/Water Colour community is running several major efforts in this regard to ensure the adoption of the FRM principles established by the Committee on Earth Observation Satellites (CEOS). Among these principles, CEOS recommends that in situ Ocean Colour radiometers (OCR) have a documented history of SI traceable calibrations including uncertainty budgets. If not then in situ measurements are unsuitable for use in validation. In addition, there can be significant differences between calibration and use of the instruments in the field due to differences in operating temperature, angular variation of the light field (especially for irradiance sensors), the intensity of the measured radiation, spectral variation of the target, among others. Each of these factors may interact with individual properties of the instrument when deployed in the field, and estimation of such uncertainties requires instrument characterization in addition to the absolute radiometric calibration if expanded uncertainties within ±10 % (k=2) are the aim. The FRM4SOC Phase 2 project -funded by the European Commission in the frame of the Copernicus Programme and implemented by EUMETSAT -contributes to these efforts, aiming at developing an operational and sustained network of radiometric measurements of FRM quality. Within FRM4SOC-2, scientists from the Tartu Observatory (TO) of the University of Tartu performed an unprecedented batch of calibrations and characterizations on a set of 37 hyperspectral field radiometers representative of the most used OCR classes within the OC community. The major conclusions of these activities are given in this study. The calibrations and characterizations performed include the determination of radiometric responsivity, long-term stability, the accuracy of the spectral scale, non-linearity and accuracy of integration times, spectral stray light, angular response of irradiance sensors in air, dark signal, thermal sensitivity, polarization sensitivity, and signal-to-noise ratio of individual OCRs. To comply with FRM, consistent correction of characterization biases and extended uncertainty analysis